Analisis Pemanfaatan Ruang Pada Daerah Resapan Air Di Kecamatan Poasia Kota Kendari - La Ode Hadini; Fitriani Fitriani; Sainur Sainur; Jufri Karim; Ahmad Hidayat (Universitas Halu Oleo, 2023)
The increase in the population in Poasia District Has an impact on the expansion of development land. This can affect the reduction in water catchment areas. This study aims to examine the use of space in water catchment areas in Poasia District. The parameters used to determine the condition of water absorption in this study, namely soil permeability, rainfall, land use and slope then processed using the Scoring, OBIA, and Overlay methods. The results of this study include the condition of water catchment in 2017 was dominated by the critical starting category of 2.850,34 acre (66,42%) while in 2021 the water catchment condition is dominated by the natural normal category covering an area of 1.920,554 acre (44,75%). Land use in water catchment areas in Poasia District in 2017-2021 which experienced the highest increase in area was settlements covering an area of 53,61 acre (36,51%) from an area of 670,91 Ha to 617,31 Ha, while land use which occurred the highest reduction in forest area of 68,26 Ha (46,50%) from an area of 2.570,05 Ha to 2.501,79 acre. Keywords: Water Infiltration, Space Utilization, GIS, Catchment area